Air and noise pollution analyses near oil and gas fields in the Mahakam Delta, Kalimantan, Indonesia - Irwansyah, Muhammad; Sunardi, Edy; Mulyo, Agung; Sendjaja, Yoga Andriana (Faculty of Geography, Universitas Gadjah Mada, 2024)
The Mahakam Delta is a strategic industrial area in East Kalimantan, Indonesia, in which oil and gas industries reduce ambient air quality and generate excessive noise. This research aimed to analyze the ambient air and noise pollution attributed to oil and gas production activities in the delta. Relevant parameters at five sampling points (UA-02 to UA-06) were measured and further analyzed in the laboratory, including total suspended particulate (TSP), SO2, Pb CO, NO2, O3, temperature, humidity, wind direction, wind speed, and noise. Indonesia’s air pollutant standard index (locally abbreviated as ISPU) with four parameters (CO, NO2, SO2, and O3) was used to determine the ambient air quality, and provisions written in the Decree of the Minister of Environment No. 50 Kep-48/MENLH/11/1996 were consulted for the noise quality assessment. Results showed ISPU values in the range of 0–50 at the five sampling points, suggesting good ambient air quality and compliance with Government Regulation No. 22 of 2021. In addition, it was revealed that the noise parameter was lower than the upper threshold set in the Ministerial Decree, namely 65 dB. Nevertheless, monitoring air and noise quality at the main pollutant sources should be regulated through policies and implemented to protect the public from exposure to potential pollutants.